The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1079/bjn19910030
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different sources of injected selenium on certain enzymes, glutathione and adenosylmethionine concentration in buffalo (Bubalus bubalis) calves

Abstract: Sodium selenite and selenomethionine were investigated as possible causative factors for the induction of Degnala disease syndrome in twelve buffalo (Bubalus bubalis) calves divided into three groups of four. Group 1 was the control group and received no additional selenium. Sodium selenite and selenomethionine were given daily as intramuscular injections on a selenium-equivalent basis, with a weekly increment in the dose of 0.05 mg Se/kg live weight from 0.05 to 0.20 mg Se/kg live weight per day, in groups 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…No significant differences in average serum selenium values post injection with Se-methionine were indicated in this trial, which was similar to findings of Pechova et al (2008) and Davidov et al (2014). However, these findings differ from those of Prased and Aora (1991) that indicated an increase in blood selenium levels following orally supplemented Se-methionine. Grace et al (2001) indicated a relationship between blood selenium (GSH-Px) and milk selenium concentrations post injection of barium selenite (Ba SeO 4 ).…”
Section: Discussioncontrasting
confidence: 99%
“…No significant differences in average serum selenium values post injection with Se-methionine were indicated in this trial, which was similar to findings of Pechova et al (2008) and Davidov et al (2014). However, these findings differ from those of Prased and Aora (1991) that indicated an increase in blood selenium levels following orally supplemented Se-methionine. Grace et al (2001) indicated a relationship between blood selenium (GSH-Px) and milk selenium concentrations post injection of barium selenite (Ba SeO 4 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Upon ingestion of 17.2 lg/ml selenium due to incorrect dosage in animal feed, pigs showed signs of acute selenium toxicity, including paralysis, hyperesthesia, anorexia, and tremors [96,121]. Signs of acute selenosis in buffalo include anorexia, alopecia, mild convulsions, and lowered body temperature [96,122]. Symptoms of chronic selenosis include hair loss, deformation or cracks on the skin, horns, and hooves of animals, resulting in the sloughing of hooves and staggering [60,96].…”
Section: Pathologies Associated With Selenium Deficiency and Toxicitymentioning
confidence: 99%
“…Additional selenite has been shown to inactivate the methionine-adenosyl transferase enzyme system and this inhibition might have prevented replenishment of SAM. Prasad and Arora (1991) observed significantly lower concentration of SAM in the liver and GSH concentration in erythrocyte in buffalo calves administered either with selenite or selenomethionine compared to the control group.…”
Section: Nitrogen and Se Balancementioning
confidence: 71%